Performance Appraisal Decision and Cognitive Processing Model: A Case of Novice and Expert Raters in the Educational Organization (Malaysian Management Journal, 2009)
This paper explores rater (novice and expert) understanding of the decision-making process in the performance appraisal system (PAS) by looking at the cognitive processing model (CPM). Interviews were conducted using a semi-structured cognitive mapping protocol involving 22 Malaysian public school administrators and were analysed using key word analysis. The decision explorer software was used to map the thinking activities involved in the rater decision-making process. The findings revealed that raters recognised the CPM steps in their performance appraisal practice. The study also identified the differences between individual novice and expert raters’ CPM in terms of concept and complexity, and also an attempt was made to compare the CPM practised by the raters with that suggested in the research framework. Every cognitive map by the raters has its own uniqueness and represents raters capability to process relevant information involved during the performance appraisal decision-making process. This paper contributes to the body of knowledge by offering a new perspective to understanding performance rating by looking at the steps involved in CPM. The research also offered some insights to policy makers, practitioners, researchers, and scholars in order to undertake further research and analysis using the steps in the CPM in a new issue, context, and environment.